Significant role of 1,25-dihydroxyvitamin D on serum calcium levels after total thyroidectomy: a prospective cohort study - Yamashita, Hiroyuki; Mori, Yusuke; Sato, Shinya; Shindo, Hisakazu; Yoshimoto, Kouichi; Tachibana, Seigo; Fukuda, Takashi; Takahashi, Hiroshi (Frontiers in Endocrinology, 2024)
Although active vitamin D (VD) has been used both preoperatively and postoperatively to prevent hypocalcemia risk in patients undergoing total thyroidectomy, the role of 1,25-dihydroxyvitamin D (1,25(OH)2D) has not been examined. This study comprehensively investigated the effects of 1,25(OH)2D on calcium (Ca) concentrations after total thyroidectomy. Methods: Serum Ca, parathyroid hormone (PTH), and 1,25(OH)2D levels were measured in 82 patients with thyroid disease before and after surgery. Results: Serum Ca, PTH, and 1,25(OH)2D levels decreased significantly on the morning of the first postoperative day. Notably, the decrease in 1,25(OH)2D concentration was significantly lower than that of PTH concentration (10.5 ± 33.4% vs. 52.1 ± 30.1%, p<0.0001), with 28% of patients showing increases in 1,25(OH)2D. The only factor predicting a postoperative 1,25(OH)2D decrease was a high preoperative 1,25(OH)2D concentration. Postoperative 1,25(OH)2D concentrations, as well as the magnitude and rate of decrease from preoperative levels, showed strong positive correlations with preoperative 1,25(OH)2D concentrations (p<0.0001 for all three variables) but not with PTH concentrations. These findings suggest that 1,25(OH)2D concentrations after thyroidectomy were more strongly dependent on preoperative concentrations than on the effect of PTH decrease and were relatively preserved, possibly preventing sudden severe postoperative hypocalcemia. A high 1,25(OH)2D level was the most important preoperative factor for hypocalcemia (<2 mmol/L; p<0.05) on the first postoperative day; however, only PTH decrease was statistically significant (p<0.001) when intraoperative factors were added. In the PTH >10 pg/mL group, the decrease in 1,25(OH)2D levels was significantly associated with postoperative hypocalcemia (p<0.05). Similarly, in the PTH levels >15 pg/mL group, a decrease in 1,25(OH)2D concentration was a significant factor, and the amount of PTH decrease was no longer significant. Conclusions: 1,25(OH)2D plays an important role in preventing sudden, severe hypocalcemia due to decreased PTH levels after total thyroidectomy, whereas high preoperative 1,25(OH)2D levels are a significant risk factor for postoperative hypocalcemia. Optimizing preoperative protocols to adjust Ca, PTH, and 1,25(OH)2D levels to improve the management of patients undergoing total thyroidectomy and to prevent extreme intraoperative PTH decreases may reduce the risk of hypocalcemia.